2021
DOI: 10.1136/bmjopen-2020-043549
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the effects of viewing visual artworks on stress outcomes: a scoping review

Abstract: ObjectiveTo review the existing evidence on the effects of viewing visual artworks on stress outcomes and outline any gaps in the research.DesignA scoping review was conducted based on the Joanna Briggs Institute methodology for scoping reviews and using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. Two independent reviewers performed the screening and data extraction.Data sourcesMedline, Embase, APA PsycINFO, Cochrane CENTRAL, Scopus, Google Scholar, Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Indeed, by examining, for example, a pivotal change often linked to engagement with art—the reduction in cortisol blood levels [ 84 ]—a foundation for the plausibility of an epigenetic framework can be easily established. The intricate regulation of cortisol and its corresponding receptor, the glucocorticoid receptor, is significantly influenced by epigenetic mechanisms, in particular by DNA methylation [ 85 ].…”
Section: Epigenetics and Aesthetic Experiences: A Focus On Music And ...mentioning
confidence: 99%
“…Indeed, by examining, for example, a pivotal change often linked to engagement with art—the reduction in cortisol blood levels [ 84 ]—a foundation for the plausibility of an epigenetic framework can be easily established. The intricate regulation of cortisol and its corresponding receptor, the glucocorticoid receptor, is significantly influenced by epigenetic mechanisms, in particular by DNA methylation [ 85 ].…”
Section: Epigenetics and Aesthetic Experiences: A Focus On Music And ...mentioning
confidence: 99%
“…Art and aesthetic experiences have been linked to improved well-being and decreased ill-being (Fancourt & Finn, 2019). For example, viewing artworks in museums has been associated with reduced stress and better psychological well-being (Clow & Fredhoi, 2006; Law et al, 2021; Ter-Kazarian & Luke, 2019). For instance, visiting an art museum (Clow & Fredhoi, 2006) or cultural sites (Grossi et al, 2019) for even short periods of 5 min to half an hour reduced the stress levels of participants (Mastandrea et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…influence aesthetic experience (Leder et al, 2012, 2014; van Paasschen et al, 2015). Relevant for our investigation, a recent review (Law et al, 2021) proposed these individual characteristics as potential moderators of the stress-reducing effect of visual artwork viewing. In support of this, Trupp et al (2023) have shown that people who are more aesthetically responsive—trait that shows ability to engage with art on all domains—also have higher well-being gains of art experience because they have better aesthetic experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reasons for which the simple contemplation of an artistic masterpiece activates the motor areas were found to derive from the possible recognition of emotions displayed by the expressions of painted persons [ 6 ], from neuron networks activated by their actions [ 7 ], from the ideal possibility to move throughout the represented scene [ 5 ], and even from the observer’s empathetic engagement, with a simulation of the motor program that corresponds to the gestures done by the artist to produce the artwork [ 7 , 8 ]. Furthermore, art observation reduces stress and blood pressure, improves cognitive and emotional processes, and distracts from negative experiences [ 9 ].…”
Section: Introductionmentioning
confidence: 99%